Potato starch quality in relation to the treatments and long-term storage of tubers - Katarzyna Brążkiewicz; Jarosław Pobereżny; Elżbieta Wszelaczyńska; Bożena Bogucka (Scientific Reports)
Abstract Starch is the most important component of potato tubers, the structure and composition of which play a key role in their utilization as well as processing and storage. Potato seed treatment may play the biggest role in ensuring proper plant growth and development. Isolated starch from tubers of different potato varieties for food processing was evaluated immediately after harvesting and after long-term storage with consideration of different products for potato seed treatment. The quality of starch was evaluated in terms of starch grain size, total starch content, pH, starch stability after freezing, gelatinization temperature as well as phosphorus and amylose content. The varieties differed significantly in starch content and quality. The Beo variety had the highest starch content in dry tuber weight (77.8%) and the best starch quality characteristics (the lowest starch stability after freezing − 18.0% and highest gelatinization temperature − 64.0 ℃ onset and 68.4 ℃ end). Simultaneous treatment of tubers with Supporter and Moncut 460 SC contributed to the highest starch content in tubers (77.6% d. m.) as well as increasing its stability after freezing (20.8%) and decreasing its gelatinization temperatures (61.7 ℃ onset and 66.0 ℃ end). This may be due to the increased proportion of large starch grains and higher amylose and phosphorus content. A slight decrease in starch quality traits was shown after long-term storage of tubers. Maintaining constant conditions during storage along with the applied treatments contributed to this. It is recommended to use products for potato seed treatment in the production technology of potato for consumption and for starch production.